Folklore, public sphere, and civil society - Muthukumaraswamy, M. D.; Kaushal, Molly (Indira Gandhi National Centre for the Arts ; National Folklore Support Centre, 2004)
In the Indian context; papers presented at a symposium held at New Delhi in 2002.